2010
DOI: 10.1128/mcb.00463-10
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Regulation of Cyclic AMP-Epac1 Signaling in Cell Adhesion by ERM Proteins

Abstract: Epac1 is a guanine nucleotide exchange factor for the small G protein Rap and is involved in membranelocalized processes such as integrin-mediated cell adhesion and cell-cell junction formation. Cyclic AMP (cAMP) directly activates Epac1 by release of autoinhibition and in addition induces its translocation to the plasma membrane. Here, we show an additional mechanism of Epac1 recruitment, mediated by activated ezrin-radixin-moesin (ERM) proteins. Epac1 directly binds with its N-terminal 49 amino acids to ERM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 70 publications
2
55
0
2
Order By: Relevance
“…This interaction regulates cell adhesion because simultaneous knockdown of all three ERM proteins decreased, but did not block completely, Epac1-induced cell adhesion (Gloerich et al, 2010). Interestingly, although all three ERM family members are expressed in A549-Epac1 cells, we found that depletion of Ezrin blocked the 007 effect in more than 70% of cells (Fig.…”
Section: Knockdown Of Ezrin and Of Core Components Of Cell Adhesion Imentioning
confidence: 75%
See 4 more Smart Citations
“…This interaction regulates cell adhesion because simultaneous knockdown of all three ERM proteins decreased, but did not block completely, Epac1-induced cell adhesion (Gloerich et al, 2010). Interestingly, although all three ERM family members are expressed in A549-Epac1 cells, we found that depletion of Ezrin blocked the 007 effect in more than 70% of cells (Fig.…”
Section: Knockdown Of Ezrin and Of Core Components Of Cell Adhesion Imentioning
confidence: 75%
“…Quantification of the cells expressing HA-RapV12 confirmed that Ezrin depletion caused a significant reduction in RapV12-induced spreading (Fig. 5C) and demonstrated that Ezrin is required for the focal adhesion formation and cell spreading induced by Rap activation, and would suggest that its role in spreading is not entirely upstream, via localisation of Epac1 (Gloerich et al, 2010), but also downstream of Rap1.…”
Section: Ezrin Is Required Downstream Of Rap Activation To Regulate Cmentioning
confidence: 77%
See 3 more Smart Citations